The Influence of TikTok Live Streaming and Discounted Prices on Purchasing Decisions - Fahmi Faturrohman; Ilham Nur Riszki Setiawan; Yusuf Yusuf; Rahmadi Rahmadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study seeks to determine how TikTok live streaming and price discounts affect student purchasing decisions at the Fashion TikTok Shop. Descriptive correlation research using quantitative techniques is the methodology used in this study. All 155 students at Fashion TikTok Shop constituted the study population, which was selected using the Slovin sampling technique. The purchase decision, price discount, and TikTok live streaming questionnaires were the instruments of this study. This research data was analyzed using multiple linear regression. Based on the results of Multiple Linear Regression analysis using the t test and F test, this study shows that TikTok live streaming at Fashion TikTok Shop influences students' purchasing decisions. Discounts affect shopping preferences at Fashion TikTok Shop. TikTok discount and live streaming influence students' shopping decisions at Fashion TikTok Shop. TikTok live streaming and discounts influence 55.2% of college students' purchases at Fashion TikTok Shop.